Pengaruh Total Aktiva Lancar, Total Utang, dan Modal Sendiri terhadap Laba Bersih pada Industri Semen Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2021 - Anggiat Erik Fernando Hutasoit (Universitas Batanghari Jambi, 2022)
The purpose of this study to Knows the effect of Current assets,total debt and total Owners’s Equity on net profit in a manner effect simultaneously and partially and which variables have the most dominant effect on net income.The analytical tool used in this research is multiple linear regression analysis,classical assumptio test. (Normality,Multicollinearity,heteroscedasticity,andautocorrelation). Hypothesis dustring test war carried out with Simultaneous (F-Test) and Partial (T-Test) statistical test. The data were tested by using Software Statistical Product and Service Solution (SPSS) 20, classical assumption testing, multiple linear regression analysis and hypotheses.On this Research the object is listed in the Indonesia Stock Exchange or BEI for 6 Years in the 2016-2021 period which selected using the purposive sampling menthod.Based on exiting sample and criteria ,researcher have 4 companies to became the sample, and the sample is :PT.INTP TBK, PT.SMGR TBK, PT.SMBR, PT.WTON,Which all of the company is selected because passing of the criteria.Result Based test on the Regression obatained linear equations Y= - 108797,404 + 0,000 – 0,010 + 0,098 + e. The results of hypothesis on the Ftest with significance = 0,05 or 5 %,then by compare value of Fcount 27,733 and Ftable = 0,05 with 3 numerator degree 3 and denominator degree is 20,this study obtained Ftable value is 3,10. And Then the number is greater tha Ftable (27,733 > 3,10 ),so Ho is rejected and ha is accepted.so all of variable by Simultaneous (Ftest) have effect to net income.Then Total Current Assets Tcount smaller than Ttable ( 0,003 < 3,10 ),so Ha rejected and Ho is accepted which means tha the variable depend positivly on net income,total debt Tcount value is smaller than Ttable (0,748 < 3,10 ) Ha rejected and Ho accepted,which means the total debt variable doesn’t have effect to Net Income,Total Owner’s equity on a Partial (Ttest ),Tcount is greater then Ttable (3,917 > 3,10 ) ,which mean’s total owner’s equity has significant effect on net income.The final result of conclusion of this study is shows that total current assets ,total debt,and total owner’s equity simultaneously have a significant effect on net income.And The Partially,total current assets doesn’t take effect for Net income,total debt has a negative effect on net income.Finally,while total owner’s equity have a significant effect on net income.